KINERJA iLEARNING RAHARJA ASK AND NEWS (IRAN) DALAM MENDUKUNG KEGIATAN TRIDHARMA IDUHELP! - Untung Rahardja; Meta Amalya Dewi; Fitri Lisnawati (Universitas Raharja, 2014)
Advances in information technology and communications which we achieve now actually been recognized and felt in the world of education in general. Currently College Prog implement a Tridharma terms Tridharma iDuHelp!. Tridharma is one of the basic responsibilities that students must be developed simultaneously and together. In this Tridharma still there are problems in the system iDuHelp! service. So IRAN (iLearning Prog Ask and News) in collaboration with iDuHelp! in providing answers and information needed by the student. In its application in Tridharma iDuHelp! IRAN There is a related method in it, such as iLearning methods that are currently being developed. With iLearning method can facilitate conduct research in detail, accurately, and clearly by using mindmapping. Besides the method of analysis is also done with three stages namely the identification of the problem, identifying needs, and identifying system requirements. In this study using 4 literature reviews that can be used as references in preparing this paper. In this article explained about the problems that arise and solving problems in accurately using the flow Flowchart. In the implementation of the prototype shown iDuHelp! As well as the performance of Iran. So the end result of the study is a system performance to information and communication media of Iran can maximize iDuHelp! care system It is widely integrated in a university.